ICT4Ag: Taking risk out of local hands - Speer, Mark (Technical Centre for Agricultural and Rural Cooperation, 2013)
The session on ‘Broadband' examined innovative ways of reducing the costs of connectivity and improving access to internet and other ICT services in remote rural areas